Pengaruh Pembelajaran TGT Menggunakan Kartu Permainan Luck and Ability Terhadap Motivasi Belajar Siswa SMP pada Materi Statistik - Wiranda Dwi Agustin; Fitri Umardiyah; M. Farid Nasrulloh (Pendidikan Matematika FKIP Universitas Mataram, 2024)
This research aims to determine the effect of mathematics learning using the TGT (Team Games Tournament) learning model assisted by luck and ability game cards on students' learning motivation in statistics material. The research method used is pre-experimental design with a one-group pretest-posttest design and uses a quantitative research approach. The subject of this research was class VIII A of Al-Furqon Middle School. The research instruments used were pre-questionnaires and post-questionnaires as well as test results as supporting data. The instrument is a questionnaire given twice (pre-questionnaire and post-questionnaire) which contains statements to measure students' learning motivation before and after implementing the TGT (Team Games Tournament) learning model. Apart from questionnaires, there are test instruments to support learning motivation data. The data analysis technique used is hypothesis testing. However, before carrying out a hypothesis test, the data obtained must first be tested for normality. Based on the calculation of the paired sample t test, it shows that the significance value is 0.000. The significance value shows 0.000 < 0.05 error level, so it can be concluded that Ha is accepted. Acceptance of this Ha means that there is an influence of TGT learning using luck and ability game cards on junior high school students' learning motivation in statistical material.